Diet‐induced obesity causes metabolic impairment independent of alterations in gut barrier integrity - Kless, Caroline; Müller, Veronika Maria; Schüppel, Valentina Luise; Lichtenegger, Martina; Rychlik, Michael; Daniel, Hannelore; Klingenspor, Martin; Haller, Dirk (Molecular nutrition & food research, 2015)
SCOPE: The causal relationship between diet‐induced obesity and metabolic disorders is not clear yet. One hypothesis is whether the obese state or high‐fat diet per se affects intestinal barrier function provoking metabolic comorbidities. METHODS AND RESULTS: In three independent experiments with AKR/J, SWR/J, or BL/6J mice, we addressed the impact of genetic background, excess body fat storage, duration of high‐fat feeding, and quality/quantity of dietary fat on glucose tolerance and gut barrier integrity in vivo and ex vivo. Impaired glucose tolerance in diet‐induced obese BL/6J and AKR/J mice was not accompanied by an altered intestinal barrier function. Enforced dietary challenge by prolonged feeding and increasing fat quantity in BL/6J mice still failed to aggravate metabolic and intestinal deterioration. Despite a low‐grade inflammatory status in adipose tissue, barrier function of BL/6J mice fed lard high‐fat diet revealed no evidence for a diet‐induced loss in barrier integrity. CONCLUSION: None of our results provided any evidence that gut barrier function is a subject to dietary regulation and obesity per se seems not to cause gut barrier impairment.